Dental Anxiety and Self-Esteem in Pediatric Patients Undergoing Maxillofacial Orthopedics - Gema Nataly Barreiro Mendoza; Thainah Bruna Santos Zambrano; Alexandra Ludwika Wied (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To investigate the correlation between dental anxiety and self-esteem in pediatric patients undergoing six months of maxillofacial orthopedic treatment in Portoviejo, Ecuador. Material and Methods: A quasi-experimental study was conducted on 92 children aged 7 to 11 with malocclusions. Participants completed a dental anxiety scale questionnaire and the House-Tree-Person (HTP) psychological graphic test before and after the installation of maxillofacial orthopedics. Confidence interval analyses were performed for qualitative variables, while mean values with standard deviations were calculated for quantitative variables. The relationship between self-esteem and dental anxiety was assessed using a chi-square test. Results: The mean age of participants was 9 years, with 86.96% residing in urban areas. Sociodemographic variables showed statistically significant differences (p<0.05). There were statistically significant differences in dental anxiety between the initial and final periods (p<0.05), with a decrease in anxiety observed after six months of treatment. As measured by the House drawing, self-esteem was significantly higher in the first period evaluated (p<0.05). Conclusion: The study found a decrease in anxiety after six months of maxillofacial orthopedic treatment. Higher self-esteem was associated with better oral health practices, highlighting the importance of the orthodontist's role in evaluating behavior to enhance treatment success and the mental health of pediatric patients.